The comparison of competitive balance in Football Premier Leagues of England, Germany, Spain, France, Italy and Iran: A case study from 2009-2010 Season - Naghshbandi, S.; Yousefi, B.; Etemad, Z.; Moradi, M. (Journal of Human Sport & Exercise, 2011)
Most sports are attractive because they are almost unpredictable. The more the competitiveness of league teams, the harder to predict the games and as a result, that league will be more attractive. Competitive balance refers to the balance in sport capabilities of teams. The aim of this paper was to compare the competitive balance in football premier leagues of Iran, England, Germany, Spain, France and Italy in 2009-2010 season. The data were secondary and collected from the final tables of premier leagues of those countries in 2009-2010 season. The five-club concentration ratio (C5) and C5 index of competitive balance (C5ICB) were used to analyze the data. The less C5ICB and C5 are, the more competitive balance is, and conversely. The C5ICB results showed that the leagues were ranked (ranging from most balance to least balance) as follows: Iran Pro League (129.60), Germany Bundesliga (135.37), French 1st League (138), Serie A, Italy (140), English Premier League (148) and Primera Liga, Spain (149.60). As a result, Iran premier league enjoyed the most balance and Primera Liga, Spain the least balance. In spite of the sport economics research representing lack of comparability between European leagues and other leagues in world, competitive balance has been decreased clearly in European leagues.